Results of the survey of the mammal fauna in the Tamdao national park, Vinhphuc province - Dang, Nguyen Xuan; Son, Nguyen Truong; Nghia, Nguyen Xuan (Academia Journal of Biology, 2014)
Rapid assessments of the mammal fauna in the Tamdao national park (NP) were conducted in December of 2004, January and May of 2005 through village interviews and extensive field investigations. Eight (8) large mammal species were reported to be extirpated from the Tamdao NP. Seventy-four (74) mammal species were recorded to be existing in the Tamdao NP. A new checklist of 77 mammal species belonging to 24 families,18 orders was compiled. Out of these 77 recorded species, 21 species were of conservation concern, including 16 nationally threatened species, 17 globally threatened species and 16 species enlisted in the Government Decree 48/2002/NDCP. Current threats to mammal fauna in the Tamdao NP were illegal wildlife hunting, wildlife trade, exploitation of forest products, forest fire and domestic cattle raising.